Investigating EFL Students' Capabilities in Grammatical Articles for Second Language Communicative Competence at an Indonesian Higher Education Context - Muhammad Fiqih Oktavian Hattah; Rusdiah Rusdiah; Ratnawati Ratnawati (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
The study aims to determine the ability to use English Articles by ABA UMI students and classify the types of difficulties in using English Articles by ABA UMI students. The study was conducted at ABA UMI using Google Form with a sample of 35 students. Data collection techniques through Interviews and essay tests were analyzed qualitatively. The results showed that the average number of students' correct answers from 20 questions was 12,1 questions or 60,71%. The average value obtained is 60,57. The Classification of students' abilities is in the